Synthesis and spectral studies of nitrogen-oxygen donor macrocyclic metal complexes of Mn(II), Cu(II) Zn(II), Pd(II) and Pt(II) - Chandra, Sulekh; Verma, Shweta; Meera, P. (Journal of the Indian Chemical Society, 2008)
The complexes of Mn(II), Cu(II), Zn(II), Pd(II) and Pt(II) with a nitrogen-oxygen donor macrocyclic ligand, viz. 5,6,13,14-dibenzo[1,4,8,11]dioxadiaza-5,7,11,13-cyclotetradecin have been synthesized and characterized by elemental analysis, molar conductance, magnetic susceptibility measurements, spectral and electrochemical studies. The molar conductance measurements of the complexes in DMF solution correspond to non electrolytic nature for M(L)X(2) complexes and 1 : 2 electrolytes for M `(L)X(2) Complexes [where M = Mn(II), Cu(II); M ` = Zn(II), Pd(II) and Pt(II); X = Cl(-), NO(3)(-), and L = ligand]. Thus, the complexes may be formulated as [M(L)X(2)] and [M `(L)]X(2) respectively. Mn(II), Cu(II) complexes were of the high-spin type whereas the complexes of Zn(II), Pd(II) and Pt(II) were diamagnetic. On the basis of spectral studies an octahedral geometry has been assigned for Mull, tetragonal for Cull, tetrahedral for Zn(II) complexes whereas square planar for Pd(II) and Pt(II) complexes.
Keywords: Cu(II); macrocyclic; Mu(II); Pd(II); Pt(II); Zn(II)